Analisis Pembangunan Ekonomi Agrikultur di Provinsi Jawa Timur - Maulana, Muhammad (Jurnal Bina Praja, 2023)
This study aims to analyze the development of the agricultural economy in each regency/city in East Java Province using the Location Quotient (LQ), Shift Share (SS), Klassen Typology, and Geographic Information System (GIS) methods. In the context of agricultural economic growth in East Java Province, this study aims to gain a deeper understanding of the contribution and development of the agricultural financial sector at the regency/city level. The LQ method was used to identify the economic, agricultural industry, and the primary economy in each regency/city. In contrast, the SS method analyzes shifts in agricultural economic growth between districts/cities. In addition, Klassen typology provides an overview of the economic quadrant groupings. Finally, GIS is used to visualize spatial analysis results, which helps identify the geographic patterns and distribution of agricultural economic development in Indonesia. This research is expected to provide valuable insights for stakeholders, including government and industry players, in planning more effective agricultural and economic development policies in each region/city. The results of this study can also be a reference for further research in East Java Province.